Chromosomal Inversion Polymorphisms in Two Sympatric Ascidian Lineages. (2nd April 2021) - Satou, Yutaka; Sato, Atsuko; Yasuo, Hitoyoshi; Mihirogi, Yukie; Bishop, John; Fujie, Manabu; Kawamitsu, Mayumi; Hisata, Kanako; Satoh, Noriyuki
Abstract: Chromosomal rearrangements can reduce fitness of heterozygotes and can thereby prevent gene flow. Therefore, such rearrangements can play a role in local adaptation and speciation. In particular, inversions are considered to be a major potential cause for chromosomal speciation. There are two closely related, partially sympatric lineages of ascidians in the genus Ciona, which we call type-A and type-B animals in the present study. Although these invertebrate chordates are largely isolated reproductively, hybrids can be found in wild populations, suggesting incomplete prezygotic barriers. Although the genome of type-A animals has been decoded and widely used, the genome for type-B animals has not been decoded at the chromosomal level. In the present study, we sequenced the genomes of two type-B individuals from different sides of the English Channel (in the zone of sympatry with type-A individuals) and compared them at the chromosomal level with the type-A genome. Although the overall structures were well conserved between type A and type B, chromosomal alignments revealed many inversions differentiating these two types of Ciona ; it is probable that the frequent inversions have contributed to separation between these two lineages. In addition, comparisons of the genomes between the two type-B individuals revealed that type B had high rates of inversion polymorphisms and nucleotide polymorphisms, and thus type B might be in the process of differentiation into multiple new types or species. Our results suggest an important role of inversions in chromosomal speciation of these broadcasting spawners.